Louis, Dauphin of France - Engraving 1745-46 - Auteur inconnu (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Louis, Dauphin of France - Engraving 1745-46. Engraved portrait of Louis, Dauphin of France (17291765)
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie